Development of a general‐purpose method for cell purification using Cre/loxP‐mediated recombination. Issue 6 (11th June 2015) - Kuroki, Shunsuke; Akiyoshi, Mika; Ideguchi, Ko; Kitano, Satsuki; Miyachi, Hitoshi; Hirose, Michiko; Mise, Nathan; Abe, Kuniya; Ogura, Atsuo; Tachibana, Makoto
Summary A mammalian body is composed of more than 200 different types of cells. The purification of a certain cell type from tissues/organs enables a wide variety of studies. One popular cell purification method is immunological isolation, using antibodies against specific cell surface antigens. However, this is not a general‐purpose method, since suitable antigens have not been found in certain cell types, including embryonic gonadal somatic cells and Sertoli cells. To address this issue, we established a knock‐in mouse line, named R26 KI, designed to express the human cell surface antigen hCD271 through Cre/loxP‐mediated recombination. First, we used the R26 Kl mouse line to purify embryonic gonadal somatic cells. Gonadal somatic cells were purified from the R26 KI; Nr5a1‐Cre‐transgenic (tg) embryos almost equally as efficiently as from Nr5a1‐hCD271‐tg embryos. Second, we used the R26 KI mouse line to purify Sertoli cells successfully from R26 KI; Amh‐Cre‐tg testes. In summary, we propose that the R26 KI mouse line is a powerful tool for the purification of various cell types. genesis 53:387–393, 2015. © 2015 Wiley Periodicals, Inc.